Combined sterile insect technique and incompatible insect technique: The first proof-of-concept to suppress Aedes aegypti vector populations in semi-rural settings in Thailand. - Pattamaporn Kittayapong; Suwannapa Ninphanomchai; Wanitch Limohpasmanee; Chitti Chansang; Uruyakorn Chansang; Piti Mongkalangoon (Public Library of Science (PLoS), 2019)
BACKGROUND:Important arboviral diseases, such as dengue, chikungunya, and Zika virus infections, are transmitted mainly by the Aedes aegypti vector. So far, controlling this vector species with current tools and strategies has not demonstrated sustainable and significant impacts. Our main objective was to evaluate whether open field release of sterile males, produced from combining the sterile insect technique using radiation with the insect incompatible technique through Wolbachia-induced incompatibility (SIT/IIT), could suppress natural populations of Ae. aegypti in semi-rural village settings in Thailand. METHODOLOGY/PRINCIPAL FINDINGS:Irradiated Wolbachia-infected Aedes aegypti males produced by the SIT/IIT approach were completely sterile and were able to compete with the wild fertile ones. Open field release of these sterile males was conducted in an ecologically isolated village in Chachoengsao Province, eastern Thailand. House-to-house visit and media reports resulted in community acceptance and public awareness of the technology. During intervention, approximately 100-200 sterile males were released weekly in each household. After 6 months of sterile male release, a significant reduction (p<0.05) of the mean egg hatch rate (84%) and the mean number of females per household (97.30%) was achieved in the treatment areas when compared to the control ones. CONCLUSIONS/SIGNIFICANCE:Our study represents the first open field release of sterile Ae. aegypti males developed from a combined SIT/IIT approach. Entomological assessment using ovitraps, adult sticky traps, and portable vacuum aspirators confirmed the success in reducing natural populations of Ae. aegypti females in treated areas. Public awareness through media resulted in positive support for practical use of this strategy in wider areas. Further study using a systematic randomized trial is needed to determine whether this approach could have a significant impact on the diseases transmitted by Ae. aegypti vector.